Performance of Higher Education Archive Institution (Study in Two Public University) - Muhammad Munadi; Fauzi Annur (Program Studi Ilmu Perpustakaan UIN Alauddin, 2021)
In the digital era, universities are required to be more accountable and professional in managing institutions’ records. Archival institutions play a fundamental role in managing all matters related to university archives. This study aims to reveal the performance of higher education archive institutions that have been carried in two universities in Indonesia which are UGM and Airlangga University. This research gathered the main sources via the universitys’ website. The method used a qualitative research methodology. While the approach used in this study is content analysis which begins with unitizing, data reduction, abductively inferring contextual phenomena, and analysis. The study found that the two universities through their archives units have performed well by following the mandate of the law. It can be seen in both website features, as well as the development in each segment is complete and explorative owned by UGM compared to Airlangga University. In addition, Airlangga University provided the AMERTA Archives Audit System (SAKA).